Stretchable Polymerized High Internal Phase Emulsion Separators for High Performance Soft Batteries. Issue 19 (13th April 2020) - Danninger, Doris; Hartmann, Florian; Paschinger, Werner; Pruckner, Roland; Schwödiauer, Reinhard; Demchyshyn, Stepan; Bismarck, Alexander; Bauer, Siegfried; Kaltenbrunner, Martin
Abstract: Powering soft embodiments of robots, machines and electronics is a key issue that impacts emerging human friendly forms of technologies. Batteries as energy source enable their untethered operation at high power density but must be rendered elastic to fully comply with (soft) robots and human beings. Current intrinsically stretchable batteries typically show decreased performance when deformed due to design limitations, mainly imposed by the separator material. High quality stretchable separators such as gel electrolytes represent a key component of soft batteries that affects power, internal resistance, and capacity independently of battery chemistry. Here, polymerized high internal phase emulsions (polyHIPEs) are introduced as highly ionically conductive separators in stretchable (rechargeable) batteries. Highly porous (>80%) separators result in electrolyte to polyHIPE conductivity ratios of below 2, while maintaining stretchability of ≈50% strain. The high stretchability, tunable porosity, and fast ion transport enable stretchable batteries with internal resistance below 3 Ω and 16.8 mAh cm −2 capacity that power on‐skin processing and communication electronics. The battery/separator architecture is universally applicable to boost battery performance and represents a step towards autonomous operation of conformable electronic skins for healthcare, robotics, and consumers. Abstract : Polymerized high internal phase emulsions are introduced as a new type of highly ionically conductive separators in stretchable batteries. High porosities (>80%) result in unprecedented low electrolyte to separator conductivity ratios, while maintaining a high stretchability of ≈50%. The battery/separator architecture universally boosts performance independent of cell chemistry. Such soft batteries power entirely untethered electronic skins.